1982
DOI: 10.1007/bf00011970
|View full text |Cite
|
Sign up to set email alerts
|

Predation of Arternia cysts by water-tiger larvae of the genus Anacaena (Coleoptera, Hydrophilidae)

Abstract: Artemia cysts are preyed upon by the larvae of Anacaena (Coleoptera, Hydrophilidae) in the wet supralittoral of the hypersaline Solar Lake near Elat . The larvae are specialized feeders of the cysts, as shown by laboratory experiments .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There are no field or experimental studies that showed predation of Corixidae, Copepopda and animals from other taxa on Artemia in the Crimean waters. However, such pieces of evidence are available from other regions (De Los Rios & Gajardo, ; Dimentman & Spira, ; Hammer & Hurlbert, ; Hurlbert et al, ; Sultana et al, ; Wurtsbaugh, ). As an example, Corixidae Trichocorixa verticalis (Fieber, 1851) appeared and reached a large number in the Great Salt Lake (Utah, USA) after a salinity decrease (Wurtsbaugh, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no field or experimental studies that showed predation of Corixidae, Copepopda and animals from other taxa on Artemia in the Crimean waters. However, such pieces of evidence are available from other regions (De Los Rios & Gajardo, ; Dimentman & Spira, ; Hammer & Hurlbert, ; Hurlbert et al, ; Sultana et al, ; Wurtsbaugh, ). As an example, Corixidae Trichocorixa verticalis (Fieber, 1851) appeared and reached a large number in the Great Salt Lake (Utah, USA) after a salinity decrease (Wurtsbaugh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Artemia can live in the broad salinity range, from 10 to 340 g/L, but in water bodies, where salinity is between 10 and 100 g/L, Artemia may be absent (Herbst, ; Shadrin, Anufriieva, & Galagovets, ; Williams, Carrick, Bayly, Green, & Herbst, ). Hammer and Hurlbert () asked: “Is the absence of Artemia determined by the presence of predators or by salinity in some saline waters?” Several studies have shown that predatory invertebrates (beetles, true bugs, mysids, copepods) and fish eating Artemia eggs, nauplii and adults can lead to the complete disappearance of Artemia in lakes–ponds or reduce their number by an order of magnitude (Anufriyeva & Shadrin, ; De Los Rios & Gajardo, ; Dimentman & Spira, ; Hammer & Hurlbert, ; Hurlbert, Loayza, & Moreno, ; Sultana et al, ; Wurtsbaugh, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge is also important to develop effective technologies to cultivate Artemia in ponds. That predation by different animal species may suppress Artemia population development has been shown in many studies (Y. V. Anufriyeva & Shadrin, 2016; de Los Rios & Gajardo, 2010; Dimentman & Spira, 1982; Hammer & Hurlbert, 1992; Hurlbert, Loayza, & Moreno, 1986; Shadrin et al, 2019; Sultana et al, 2011; Wurtsbaugh, 1992). Gammarus aequicauda (Martynov, 1931) is a widespread and abundant amphipod species in estuaries, marine lakes, lagoons, and brackish waters of the Mediterranean and the Black Sea (E. V. Anufriieva & Shadrin, 2020; Balushkina, Golubkov, Golubkov, Litvinchuk, & Shadrin, 2009; Delgado, Guerao, & Ribera, 2011; Greze, 1977).…”
Section: Introductionmentioning
confidence: 88%